Comparative Effects of Group and One to One Speech and Language Therapy on Language Development of Hearing Impaired Children - Atia Ur Rehman; Muhammad Sikander Ghayas Khan; Munawer Ahmed Malik; Naseer Ud Din (Journal Riphah College of Rehabilitation Sciences, 2016)
Background: Children with hearing impairment face speech and language deficits throughout their lives; hence they develop non speaking attitudes. Speech and language therapies are planned to develop oral/verbal language skills in students with hearing impairment. The therapy may be individualized or in groups depending upon time, duration, resources and extent of disability. This study aimed to find the effectiveness of group and individual therapy on language development of hearing impaired students. The population comprised hearing impaired students in Lahore district. The sample constituted twenty students from class one randomly selected and having a severe to profound degree of hearing loss. A quasi experimental study based on pre-posttest design. The findings are indicative of effectiveness of group approach as compared to the individualized therapy.